Land use change, modelling of Soil Salinity and households’ decisions under Climate Change Scenarios in the Coastal Agricultural Area of Senegal - Thiam, Sophie (2021)
A thesis submitted to the department of Civil Engineering, College of Engineering in partial fulfilment of the requirements for the degree of Doctor Of Philosophy in Climate Change and Land Use.